STARTING YOUR CAREER IN PUBLIC ACCOUNTING. - Harvey, John L. (The Accounting Review, 1955)
The article focuses on starting a career in public accounting. To make it worth one's while to enter the field of public accounting, one must have a considerable portion of courage, strong ambition and a full measure of persistence. One must be willing and physically able to work hard. A career in public accounting calls for long hours of high quality work, frequently done under pressure. A man without fortitude should look elsewhere for a career. A successful accountant must have imagination. The public accountant is not a human calculator who arranges data fed into him. He is a man with the ability to visualize the abstract, to see as a finished product a work paper, an audit program, a report, an accounting system before it has ever come into existence. Perhaps the thing that one should do that is of the greatest importance is to provide oneself with a sound formal education. There is a trend toward ever increasing the educational requirements for the certified public accountant.